A cluster development approach to enhance smallholder farmers' market access and economies of scale in South Africa: perspectives of agricultural sector implementation experiences - Ramolotja, Peter (University of the Free State, 2025)
The study aims to investigate the use of a cluster development approach in helping smallholder farmers achieve economies of scale and participate in the market sustainably. It focused on the potato producers who are producing for the market and belong to a cluster, specifically the 12 smallholder farmers belonging to the Blouberg potato cluster. The research employed the qualitative research approach because it is inclined to seek understanding and meaning of a phenomenon and to capture people's lived experiences. It was chosen because it allows the researcher to gather in-depth information by allowing people to describe a phenomenon according to their understanding and perspectives. With its naturalistic nature, the approach generates rich data, allowing the researcher to understand the phenomenon comprehensively. The study found that a successful cluster consists of companies that have strong relationships to enable the flow of information and skills. In the cluster, farmers became friends before farming, resulting in high levels of trust. Institutions involved in supporting farmers include the Land Bank, PotatoSA, MAFISA, Kgodiso Financial Services and the Government. Additionally, the cluster is located in an area endowed with natural resources that support the planting of potatoes throughout the year. The success of the cluster is also based on the entrepreneurial spirit of the individual farmers. Many of the farmers started small, using meagre resources to grow their businesses. They attained economies of scale by reducing transaction costs through collective marketing, sharing inputs, machinery and transportation. The study recommends the creation of a conducive environment for creating strong relations among the farmers. It also recommends the involvement of further training institutions in the training of the farmers; the promotion of vocational and business incubation; farmers belonging to commodity organizations; coordinated procurement of inputs and marketing; selection of location that provides a competitive edge and the support from the government in the form of extension services, infrastructure and production inputs.
Dissertation(MDS (Development Studies))--University of the Free State, 2025
Keywords: Smallholder farmers; Cluster development approach; Market participation; Potato producers; Economies of scale